In triangle ABC; AD⊥BC. Prove that AC²= AB² + BC²-2BCBD.
FIGURE IS GIVEN IN ATTACHMENT
Attachments:
![](https://hi-static.z-dn.net/files/d95/8b496bab5f3b7548666d32b83152a1e4.jpg)
Answers
Answered by
3
In the right angle triangle ABD, we have
AD² = AB² - BD²
In the right angle triangle ACD we have
AD² = AC² - CD²
So AC² - CD² = AB² - BD²
=> AC² = AB² + CD² - BD²
=> = AB² + (CD + BD)* (CD - BD )
= AB² + BC * [(BC - BD) - BD]
= AB² + BC * [ BC - 2 BD ]
= AB² +BC² - 2 BC * BD
Hope it helps
Plz mark as brainliest.
Answered by
1
Step-by-step explanation:
Solve this question please
Attachments:
![](https://hi-static.z-dn.net/files/df0/f8af4b07535480eb4d1f4910c517ced1.jpg)
Similar questions